PRESIDEN JOKO WIDODO DALAM BINGKAI MEDIA MASSA - Suharyo Suharyo; Surono Surono; M. Farikhul A (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aimed to describe the ideology of: (a) journalists, (b) politicians, and (c) observers/community in framing President Joko Widodo in Suara Merdeka, Kompas, andRepublika daily newspapers. The data sources were the three newspapers published in2016. The data were collected through: (a) literature study, (b) discourse analysis, and(c) in-depth interviews with linguists and mass media experts. The data analysis wascarried out using Pan and Kosicki’s framing analysis model. The results show that thereare ideological differences among the three media in framing President Joko Widodo. Thedifferences are manifested in the aspects of: (a) syntax, (b) script, (c) theme, and (d) rhetoric.The three media also differ in presenting: (a) news schemes, (b) news completeness, (c)details, (d) lexicon, and (e) completeness of 5W + 1H elements in reporting PresidentJoko Widodo.Keywords: frame, ideology, media, framing analysis